How are Developing Countries Coping with Higher Oil Prices? - Bacon, Robert; Kojima, Masami (World Bank, Washington, DC, 2014)
This note is based on a forthcoming report by ESMAP. The report covers policy alternatives adopted by developing country governments in response to the increases in world oil prices since the end of 2003. The report analyzes what factors have affected the responses and what policy prices have been used by governments to mitigate the effects of higher oil prices on consumers, the government budget, and the total demand for oil.